2018
DOI: 10.1016/j.ejca.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density and breast cancer risk in breast screening assessment cases and women with a family history of breast cancer

Abstract: BackgroundMammographic density has been shown to be a strong independent predictor of breast cancer and a causative factor in reducing the sensitivity of mammography. There remain questions as to the use of mammographic density information in the context of screening and risk management, and of the association with cancer in populations known to be at increased risk of breast cancer.AimTo assess the association of breast density with presence of cancer by measuring mammographic density visually as a percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 42 publications
2
47
0
2
Order By: Relevance
“…20,21 Young women with dense mammary tissue were threefold likely to develop breast cancer than their counterparts. Similar results have been found by Duffy et al 22 The estrogens levels in women with dense breast may not be involved in the occurrence of breast cancer. 23 Carcinogenesis would certainly be related to higher cell volume than in women with less dense breasts.…”
Section: Discussionsupporting
confidence: 90%
“…20,21 Young women with dense mammary tissue were threefold likely to develop breast cancer than their counterparts. Similar results have been found by Duffy et al 22 The estrogens levels in women with dense breast may not be involved in the occurrence of breast cancer. 23 Carcinogenesis would certainly be related to higher cell volume than in women with less dense breasts.…”
Section: Discussionsupporting
confidence: 90%
“…A deep learning method proposed by Lehman et al 45 for assessing BI-RADS density in a clinical setting, showed good agreement between the model's predictions and radiologists' assessments. Duffy et al 46 investigated the association of different density measures with breast cancer risk using digital breast tomosynthesis and compared automatic and visual measures. All measures showed a positive correlation with cancer risk, but the strongest effect was shown by an absolute density measure.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations can affect all automated breast density methods. However, Volpara seems to provide a better correlation with visual assessment of breast density as noted by Duffy et al 57 who analyzed both Volpara and Quantra software, which helps to justify our choice of comparison in this research. Vinnicombe also prefers Volpara to Cumulus.…”
Section: Discussionmentioning
confidence: 72%